The DosR Regulon Modulates Adaptive Immunity and Is Essential for Mycobacterium tuberculosis Persistence - Mehra, Smriti (Am J Respir Crit Care Med, 2015)
Rationale: Hypoxia promotes dormancy by causing physiologic changes to actively replicating Mycobacterium tuberculosis. DosR controls the response of M. tuberculosis to hypoxia. Objectives: To understand DosR's contribution in the persistence of M. tuberculosis, we compared the phenotype of various DosR regulon mutants and a complemented strain to M. tuberculosis in macaques, which faithfully model M. tuberculosis infection. Methods: We measured clinical and microbiologic correlates of infection with M. tuberculosis relative to mutant/complemented strains in the DosR regulon, studied lung pathology and hypoxia, and compared immune responses in lung using transcriptomics and flow cytometry. Measurements and Main Results: Despite being able to replicate initially, mutants in DosR regulon failed to persist or cause disease. On the contrary, M. tuberculosis and a complemented strain were able to establish infection and tuberculosis. The attenuation of pathogenesis in animals infected with the mutants coincided with the appearance of a Th1 response and organization of hypoxic lesions wherein M. tuberculosis expressed dosR. The lungs of animals infected with the mutants (but not the complemented strain) exhibited early transcriptional signatures of T-cell recruitment, activation, and proliferation associated with an increase of T cells expressing homing and proliferation markers. Conclusions: Delayed adaptive responses, a hallmark of M. tuberculosis infection, not only lead to persistence but also interfere with the development of effective antituberculosis vaccines. The DosR regulon therefore modulates both the magnitude and the timing of adaptive immune responses in response to hypoxia in vivo, resulting in persistent infection. Hence, DosR regulates key aspects of the M. tuberculosis life cycle and limits lung pathology.